CHARACTERIZATION OF (Mg0.6Zn0.4)TiO3 CERAMICS AS DIELECTRIC RESONATOR MATERIALS IN MICROWAVE FREQUENCIES - Syah Nanta Maulana Ishak; Frida Ulfah Ermawati (Spektra: Jurnal Fisika dan Aplikasinya, 2022)
Ceramics based on magnesium titanate (MgTiO3) are dielectric materials that have the potential to be used in telecommunications systems at microwave frequencies, such as filters, antennas, and signal generators. This study aims to characterize the resonant frequency and output power of (Mg0.6Zn0.4)TiO3 ceramics (abbreviated MZT04) as a dielectric resonator (DR) material in a DRO circuit and relate it to the structure, microstructure, and bulk density data of the ceramics. The MZT04 ceramics were fabricated by compacting MZT04 powder at a pressure of 2.5 MPa using a cylindrical die press of 5 mm in diameter to become pellets with the same diameter. The pellets were sintered at 1300 ℃ by varying holding time for 6, 8, and 10 h to become ceramics. Data on the structure of the ceramics were obtained from the X-Ray Diffraction (XRD) pattern with Cu-Kα radiation which showed that the three ceramics contained MgTiO3 phase, each 87.02; 90.55; and 87.40 % molar, the rest % is MgO and TiO2 rutile phases. The increase in sinter holding time has increased the unit cell volume of the MgTiO3 phase from (307.94), (308.61), to (308.94) Å3; the size of the lattice parameters (a=b, c) also increased from (5.057, 13.903) Å, (5.058, 13.903) Å, to (5.061, 13.914) Å; like wise, the bulk density increased from 2.51, 2.82, and 3.04 g/cm3. As a DR material, the three ceramics exhibit a resonant frequency signal each at 5.20; 5.21; and 5.22 GHz with the output power of -19.70; -14.47; -15.70 dBm, and the FWHM of the signal is 59.3; 61.6; and 61.2 MHz. Therefore, MZT04 ceramics can be applied as the DR material in microwave frequencies, especially at ~5.20 GHz. The variations in sinter holding time is not significant effect on the position of the resonant frequency.